Endovascular Treatment of a Giant Aneurysm of the Maxillary Artery - J. A. Stephenson; S. Panteleimonitis; E. Choke; M. Dennis; M. Glasby (Case Reports in Vascular Medicine)
Aneurysms of the maxillary artery are rare and the majority of the literature refers to false aneurysms. We report the first case of what we believe to be a spontaneous true maxillary artery aneurysm and its endovascular management.